Integrated analysis of the whole transcriptome of skeletal muscle reveals the ceRNA regulatory network related to the formation of muscle fibers in Tan sheep - Cui, Ran; Kang, Xiaolong; Liu, Yufang; Liu, Ximing; Chan, Shuheng; Wang, Yubei; Li, Zhen; Ling, Yao; Feng, Dengzhen; Li, Menghua; Lv, Fenghua; Fang, Meiying (Frontiers in Genetics, 2022)
Muscle fiber type has an important effect on meat quality, and meat quality can be significantly improved by increasing the proportion of slow-twitch fibers. However, it is unclear which genes determine the formation of muscle fibers and how they regulate the formation of muscle fibers in sheep. In this study, we attempted to characterize the expression profiles of coding and noncoding RNAs in muscle tissue from Tan sheep and Dorper sheep by high-throughput RNA sequencing. Two different muscle tissues, longissimus dorsi and biceps femoris, were collected from Tan sheep and Dorper sheep to explore their molecular mechanisms of the formation of muscle fibers. The expression profiling revealed that 214 lncRNAs, 25 mRNAs, 4 miRNAs and 91 circRNAs had significantly different levels of expression in the longissimus dorsi of Tan sheep and Dorper sheep. Similarly, the expression profiling revealed that 172 lncRNAs, 35 mRNAs, 12 miRNAs and 95 circRNAs was significantly differentially expressed in the biceps femoris of Tan sheep and Dorper sheep. GO and KEGG annotation revealed that these differentially expressed genes and noncoding RNAs were connected to the formation of muscle fibers pathways, such as the FoxO, AMPK and Ca2+ signaling pathway. Several key genes involved in the formation of muscle fibers, including ACACB, ATP6V0A1, ASAH1, EFHB, MYL3, C1QTNF7, SFSWAP and FBXL5. RT–qPCR verified that the expression patterns of randomly selected differentially expressed transcripts were highly consistent with those obtained by RNA sequencing. Potential lncRNA/circRNA–miRNA–gene interactions were also examined. A total of 9 lncRNAs, 16 miRNAs, 40 circRNAs and 19 genes formed lncRNA/circRNA–miRNA–gene networks, suggesting that complex regulatory networks of coding and non-coding genes underlie the formation of muscle fiber in Tan sheep. Our results showed that some ceRNA subnetworks, such as circ_0017336-miR-23a-FBXL5, may play a crucial role in the regulation the formation of muscle fibers, which provides a useful resource for further research on formation of muscle fibers in sheep. The results extend our knowledge about the diversity of the formation of muscle fibers among different domestic animals and provide a foundation for studying novel mechanisms that control the formation of muscle fibers in Chinese indigenous sheep.